2011
DOI: 10.1590/s0004-27492011000200015
|View full text |Cite
|
Sign up to set email alerts
|

Lesão escleral durante o agulhamento com mitomicina C: relato de caso

Abstract: RESUMOPaciente de 70 anos foi submetida à cirurgia de catarata e glaucoma no olho esquerdo em 1996. Onze anos depois, com a pressão intraocular descontrolada (32 mmHg), foram realizados dois agulhamentos episclerais com mitomicina-C, na tentativa de recuperar a função da trabeculectomia. Após o segundo agulhamento, a paciente evoluiu com importante hiperfiltração, atalamia grau III e iminente descompensação da córnea. Foi tentado o tratamento clínico com corticóide, cicloplégico, inibidores da produção do aquo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Temporary conjunctival leakage, small hyphemas and temporary shallowing of the anterior chamber have been reported (18,27). However, some reports have suggested more severe complications when performing needling in flat and scarred blebs (28,29). In our study, we observed complications in three eyes (15%); only one eye required further surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Temporary conjunctival leakage, small hyphemas and temporary shallowing of the anterior chamber have been reported (18,27). However, some reports have suggested more severe complications when performing needling in flat and scarred blebs (28,29). In our study, we observed complications in three eyes (15%); only one eye required further surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, alguns autores sugerem complicações mais severas, quando realizaram o agulhamento em bolhas planas ou cicatrizadas 65,66 . Neste estudo, relataram-se complicações em três olhos (15%), e em um foi necessária intervenção cirúrgica reparadora.…”
Section: Critérios De Sucesso E De Exclusãounclassified